Changes over 10 years in the nursing workforce in Guangdong province, China: Three‐wave multisite surveys. (19th August 2021) - Liu, Jiali; Liu, Xu; Zheng, Jing; Liu, Ke; Wu, Yan; Wang, Jun; Li, Mengqi; You, Liming
Abstract: Aims: The study aimed to describe the changes in the nursing workforce in 2008–2018 in Guangdong province, China. Background: A strong nursing workforce is important in the development of the health care system in China. However, whether the nursing workforce in China has improved is underexplored. Methods: Three waves of surveys were conducted in hospitals in Guangdong province, China, in 2008, 2014 and 2018. Findings: The proportion of less experienced nurses and nurses holding a bachelor's degree has increased. The hospital nurse‐to‐patient ratio did not change significantly. The work environment deteriorated from 2008 to 2014 and improved from 2014 to 2018. Nurse‐perceived staffing adequacy and nurses participating in hospital administration were scored lowest. The nurse–physician relations declined from 2008 to 2018. Nurse satisfaction, retention and quality of care improved, while reduced personal accomplishment deteriorated. Conclusion: The nursing workforce in Guangdong province, China, is young and highly educated. Nurse outcomes and quality of care have made progress from 2008 to 2018. Nurse staffing and burnout remain matters of concern. Implications for nursing management: Strategies addressing nursing workforce issues in China include dealing with the nursing shortage, establishing pathways for nurses' participation in decision‐making, increasing nurses' income and welfare, promoting recognition of nurses and improving the quality of care.